2009
DOI: 10.1128/jvi.01627-08
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis of Small-Ruminant Lentivirus Genotype E: a Caprine Lentivirus with Natural Deletions of the dUTPase Subunit, vpr -Like Accessory Gene, and 70-Base-Pair Repeat of the U3 Region

Abstract: The nucleotide sequence of the highly divergent small-ruminant lentivirus genotype E has been determined. The full genome consists of 8,418 nucleotides and lacks two large portions corresponding nearly to the entire dUTPase subunit of the pol and vpr-like accessory genes. Moreover, the 70-bp repeat of the U3 region of the long terminal repeat was observed to be deleted. Interestingly, this lentivirus genotype is able to persist in a local breed population, and retrospective analysis revealed its presence in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 23 publications
0
39
1
1
Order By: Relevance
“…Genotype E1 was firstly discovered in the Roccaverano goat breed from Piedmont (Italy) as a highly divergent SRLV [38]. Analysis in vivo showed that although the virus does not cause detectable pathological signs; genotype E is prevalent and has been hiding from standard serological tests, due to its highly divergent structural proteins, and has also been inadvertently undetected by breeders and practitioners, due to the absence of symptoms.…”
Section: Live Attenuated Vaccinesmentioning
confidence: 99%
“…Genotype E1 was firstly discovered in the Roccaverano goat breed from Piedmont (Italy) as a highly divergent SRLV [38]. Analysis in vivo showed that although the virus does not cause detectable pathological signs; genotype E is prevalent and has been hiding from standard serological tests, due to its highly divergent structural proteins, and has also been inadvertently undetected by breeders and practitioners, due to the absence of symptoms.…”
Section: Live Attenuated Vaccinesmentioning
confidence: 99%
“…A previously described ELISA test was used to serotype samples, consisting of 109 P16-25 recombinant antigen derived from genotypes B (strain IT-Pi1) and E 110 (strain Roccaverano) (Reina et al, 2009a). Briefly, ELISA microplatesA c c e p t e d M a n u s c r i p t 7 (Immunomaxi TPP) were coated with 100 ng of each recombinant antigen and 112 water as negative control.…”
Section: Elisa Comparative Assays 108mentioning
confidence: 99%
“…These viruses induce persistent infections in goats and sheep, and less frequently in wild ruminants (Bertoni & Blacklaws, 2010;Bertoni & Blatti-Cardinaux, 2016;Minardi da Cruz, et al, 2013 ). Clinical manifestations such as arthritis, mastitis, pneumonia and leukoencephalomyelitis occur only in a minority of the infected individuals, depending on the genetic background of the animals and the virulence of the infecting strain (Blacklaws, 2012;Heaton et al, 2012;Ramirez et al, 2013;Reina et al, 2009;White & Knowles, 2013). SRLV are principally transmitted from mother to offspring via ingestion of infected milk or colostrum, and by aerosol between animals in close contact (Blacklaws et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analyses showed that all the virulence genes, such as vif, dUTPase and vpr (tat), were intact and could not explain the low virulence of these strains. Indeed, SRLV strains carrying natural or targeted mutations of these virulence genes were shown to be attenuated in vivo (Grego et al, 2007;Harmache et al, 1995aHarmache et al, , b, 1996aKristbjornsdottir et al, 2004;Reina et al, 2009;Turelli et al, 1996Turelli et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%